Management and Reconstruction of a Gastroesophageal Junction Adenocarcinoma Patient Three Years after Pancreaticoduodenectomy: A Surgical Puzzle - Dionysios Dellaportas; James A. Gossage; Andrew R. Davies (Case Reports in Surgery)
Introduction. With the improving survival of cancer patients, the development of a secondary primary cancer is an increasingly common phenomenon. Extensive surgery during initial treatment may pose significant challenges to surgeons managing the second primary cancer. Case Presentation. A 69-year-old male, who had a pancreaticoduodenectomy three years ago for pancreatic head adenocarcinoma, underwent an uneventful extended total gastrectomy for gastroesophageal junctional adenocarcinoma. The reconstruction controversies and considerations are highlighted. Discussion. Genetic, environmental, and lifestyle factors are common for several gastrointestinal malignancies. However, the occurrence of a second unfavorable cancer such as gastroesophageal adenocarcinoma after pancreatic head cancer treatment is extremely uncommon. This clinical scenario possesses numerous difficulties for the surgeon, since surgical resection is the mainstay of treatment for both malignancies. Gastrointestinal reconstruction becomes challenging and requires careful planning and meticulous surgical technique along with sound intraoperative judgement.